Wastewater monitoring of SARS-CoV-2 in on-grid, partially and fully off-grid Bedouin communities in Southern Israel - Yaniv, Karin; Craddock, Hillary A.; Mahameed, Fareed; Shagan, Marilou; Salah, Ikram; Lakkakula, Satish; Resnick, Keren; Haber, Corinne; Davidovitch, Nadav; Moran-Gilad, Jacob; Kushmaro, Ariel; Lipchin, Clive (Frontiers in Water, 2023)
Background: Wastewater based epidemiology (WBE) has become an important tool in SARS-CoV-2 surveillance and epidemiology. While WBE measurements generally correlate with observed case numbers in large municipal areas on sewer grids, there are few studies on its utility in communities that are off-grid (non-sewered). Methods and Materials: To explore the applicability of wastewater surveillance in our region, five Bedouin communities along the Hebron Stream in Southern Israel (Negev desert) were sampled. One point (El-Sayed) represents a community with partial connection to the sewer grid system and another point (Um Batin) represents a community with no access to the sewer grid system. The towns of Hura, Lakia, and Tel Al-Sabi/Tel Sheva were on-grid. A total of 87 samples were collected between August 2020 to January 2021 using both grab and composite sampling. RNA was extracted from the raw sewage and concentrated sewage. RT-qPCR was carried out with N1, N2, and N3 gene targets, and findings were compared to human case data from the Israeli Ministry of Health. Results: SARS-CoV-2 was detected consistently over time in on-grid Bedouin towns (Lakia, Tel Sheva/Tel as-Sabi, and Hura) and inconsistently in smaller, off-grid communities (El-Sayed and Um Batin). The trend in maximum copy number/L appears to be driven by population size. When comparing case numbers normalized to population size, the amounts of gene copies/L was inconsistently related to reported case numbers. SARS-CoV-2 was also detected from sewage-impacted environmental waters representing communities with no access to the wastewater grid. When grab sampling and composite sampling data were compared, results were generally comparable however composite sampling produced superior results. Conclusions: The mismatch observed between detected virus and reported cases could indicate asymptomatic or "silent" community transmission, under-testing within these communities (due to factors like mistrust in government, stigma, misinformation) or a combination therein. While the exact reason for the mismatch between environmental SARS-CoV-2 signals and case numbers remains unresolved, these findings suggest that sewage surveillance, including grab sampling methodologies, can be a critical aspect of outbreak surveillance and control in areas with insufficient human testing and off-grid communities.